Professional partnerships in children's services : working together for children - Nolan, Andrea; Cartmel, Jennifer; Macfarlane, Kym (Australia : Early childhood Australia Inc, 2014)
Early childhood education and care services in Australia are moving towards an integrated approach to service delivery requiring educators to work in partnership with professionals from sectors such as health, education and community services for the benefit of young children and their families. This means that educators need to work in perhaps new and different ways in their everyday work.
Includes bibliographical reference and index.
Keywords: Child development -- Australia; Early childhood education -- Australia; Education, Preschool